Using WordPress as a library content management system - Jones, Kyle M. L (Library technology reports, 2011)
Authors Kyle M.L. Jones and Polly-Alida Farrington, along with several librarian contributors, deliver a richly illustrated, practical guide for using WordPress as a tool for managing digital content, from basic set-up to customization with plugins